Most common diagnoses and antibiotics used in South American Camelid patients at a university clinic in Austria - Hund, Alexandra; Wittek, Thomas; Selan, Ursa; Käsbohrer, Annemarie; Firth, Clair L. (Frontiers in Veterinary Science, 2023)
Knowledge of common diseases and their treatment in minor species, such as llamas and alpacas, is growing, but frequently drugs are not licensed in these species. Our aim was to evaluate frequent diagnoses and commonly applied antibiotics in patients of a university clinic with a particular focus on EMA Category B antibiotics, which are critically important for human health. We retrospectively analyzed anonymized patient records between 2005 and 2019 regarding the causes for antibiotic treatment and choice of antibiotic substance.The most frequent indications for antibiotic treatment were diseases of the digestive tract and perioperative prophylaxis for castrations. The number of applications of EMA Category B antibiotics initially increased with the number of patients treated, then remained stable, while the use of Category D drugs increased over time. Most Category B antibiotics were used for diseases of crias and diseases of the digestive tract, primarily dental disease. The use of EMA Category B antibiotics cannot be completely avoided based on the types of cases treated. However, antibiotic stewardship guidelines should be followed wherever possible.